2019
DOI: 10.1155/2019/1731540
|View full text |Cite|
|
Sign up to set email alerts
|

Adipose-Derived Stromal Cells Attenuate Adipose Inflammation in Obesity through Adipocyte Browning and Polarization of M2 Macrophages

Abstract: Obesity is a metabolic condition associated with multiple health problems such as endocrine and metabolic dysfunction and chronic inflammation in adipose tissues. In this study, the ADSCs could be stimulated to differentiate into brown adipocyte with rosiglitazone treatment based on the Oil-Red-O staining trial. Furthermore, the multilocular lipid droplets located in the center was increased in differentiated brown adipocytes, and brown fat-associated proteins, UCP1, PPAR-γ, and LPL were highly expressed in br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…It had already been shown that proinflammatory M1 macrophages infiltrating BAT impair its ability to appropriately respond to thermogenic stimuli, by the secretion of TNFα and IL‐1β that suppress the induction of Ucp1 gene expression [48,49]. Since Mcpip1 inhibits the classic activation of M1 macrophages and promotes M2 polarization, we postulate that the hypothermia of Mcpip1 fl/fl LysM Cre mice might be at least partially explained by an increased infiltration of M1 macrophages into BAT and a high level of Tnfa [29,50].…”
Section: Discussionmentioning
confidence: 91%
“…It had already been shown that proinflammatory M1 macrophages infiltrating BAT impair its ability to appropriately respond to thermogenic stimuli, by the secretion of TNFα and IL‐1β that suppress the induction of Ucp1 gene expression [48,49]. Since Mcpip1 inhibits the classic activation of M1 macrophages and promotes M2 polarization, we postulate that the hypothermia of Mcpip1 fl/fl LysM Cre mice might be at least partially explained by an increased infiltration of M1 macrophages into BAT and a high level of Tnfa [29,50].…”
Section: Discussionmentioning
confidence: 91%
“…This reduced body mass and serum levels of very low density lipoprotein (VLDL) and low density lipoprotein (LDL) cholesterol and increased high density lipoprotein (HDL) cholesterol levels in recipients. 54 However, some studies have indicated the limitations of such strategies in clinical applications. 18,55 Primary concern is that the period of ASC proliferation and differentiation potential in vivo is short and negatively correlated with age.…”
Section: Effects Of Bat Transplantation On Metabolic Diseasesmentioning
confidence: 99%
“…Specifically, transplanted mice show increased oxygen consumption, respiratory rate, and overall energy consumption. 54 For all these important findings, there are still a number of hurdles associated with iPSC-based therapy that will need to be overcome.…”
Section: Brown-like Adipocytes Derived From Induced Pluripotent Stem ...mentioning
confidence: 99%
“…The immunomodulatory effects of MSCs have been observed in obesity. As described by Zhang et al., adipose-derived stem cells (ADSCs) suppress pro-inflammatory cytokines TNF-α, IL-6, and IL-1β in the obese mice through inhibition of the ITGAM/NF-κB pathway and polarisation of M2 macrophages [ 154 ]. Another recent study found that lean mouse-derived ADSCs treatment successfully reduced obesity-associated white adipose tissue inflammation and substantially improved insulin action in obese mice by re-modulating the phenotypes of adipose-resident macrophages from pro-inflammatory M1 toward anti-inflammatory M2 subtypes [ 155 ].…”
Section: Prospects In Obesity-induced Oa Treatmentmentioning
confidence: 99%